Institutional Strengthening for the Enforcement of the Code of Ethics and Conduct for Constitutional Court Judges - Ayuni, Sinda Eria; Ismawati, Ismawati (East Asian Journal of Multidisciplinary Research, 2024)
A decision of the MKMK that is’nt based on the Constitutional Court Regulation makes the dignity of the constitutional court begin to be questioned and doubted by the public. This research analyze and recommend an ideal design for the Constitutional Judges Code of Ethics and Conduct Enforcement Institution as an effort to strengthen the Constitutional Court's position. The research method uses normative juridical. The research approaches used are a statutory approach, a conceptual approach. The results is the future MKMK membership arrangement will not include active Constitutional Court judges. Members of the MKMK will be selected by an ad hoc panel of experts, with the goal of choosing professional MKMK members who will maintain the dignity of Constitutional Court judges.